Proving predatory pricing in European Union Competition law - Ana Pošćić (Zbornik Radova Pravnog Fakulteta u Splitu, 2012)
Article 102 of the Treaty on the Functioning of the European Union prohibits abuse of a dominant position by one or more undertakings within the common market. One of abuse forms being especially difficult to prove is predatory pricing. This paper attempts to find parameters to be helpful in distinguishing normal competition where undertakings with their better products and products of higher quality squeeze out competitors from predatory behaviour situations. To differentiate acceptable from illicit behaviours the so-called AKZO test is applied under which a predatory price is determined by cost analysis assuming that the prices below average variable costs are predatory prices. Prices above average variable costs but below average total costs will not be predatory prices, unless they are a part of a policy of elimination of competition. Therefore, the relation between price and costs will be taken into consideration, where, under certain circumstances, it will be supplemented with test of intention. Although opinions that the AKZO test should be combined with the recoupment test appear in the doctrine, it seems that the test based on costs is still sufficient by taking into account the strategies and behaviours of undertakings.